THE ABILITY OF THE CONTINUOUSLY VARIABLE TRANSMISSION TO CONTROL THE ENGINE AT MAXIMUM POWER: LITERATURE REVIEW - Sugeng Ariyono; Bambang Supriyo; Indra Feriadi; Dedy Ramdhani Harahab; Nurul Akmar Akmar Abu Husain (SINERGI, 2021)
Good ride performance is one of the most important key attributes of a passenger vehicle. One of the methods to achieve this is by using Continuously Variable Transmission (CVT). This is because a CVT can provide an almost infinite ratio within its limits smoothly and continuously. The flexibility of a CVT allows the driving shaft to maintain a constant angular velocity over a range of output velocities. New developments in gear reduction and manufacturing have led to ever more robust CVTs, allowing them to be applied in more diverse automotive applications. As CVT development continues, costs will be reduced further, and the performance will continue to improve, making further development and application of the CVT technology desirable. This cycle of improvement will offer CVT a solid foundation in the world's automotive infrastructure. This paper aims to provide some background and relevant information that is necessary for this study. Specifically, a brief description of CVT, advantages and their brief history is presented. This paper also evaluates the current state of CVT, investigate the technology frontline of drivetrain control and the development of CVT. The stepless transmission is able to maintain the engine running at its maximum power.